A different lens?: how ethnic minority media cover crime - Douai, Aziz (Canadian journal of criminology and criminal justice, 2018)
There is a growing body of literature on the nexus of media, race, and crime, which reveals that crime is exaggerated in mainstream media and that these same venues tend to racialize crime and criminalize race. The impact of this is that inaccurate public perceptions about the frequency, seriousness, and demographic distribution of crime are reinforced. Interestingly, however, there have been no focused efforts to explore the ways in which crime is featured within the media targeting specific racial and ethnic communities. We know little about whether such outlets reproduce these patterns. This pilot [End Page 96] study is intended to initiate an examination of the representation of crime news in Canada's ethnic media, exploring the patterns of crime reporting in such outlets and comparing the ways in which such news is presented to different audiences. We conducted a content analysis of two English-language newspapers in the Greater Toronto Area, which nonetheless serve specific racial and ethnic communities. Quantitative (e.g., frequency) and qualitative (e.g., themes) findings from the study offer insights into crime reporting patterns, as well as the nature of crime coverage in the studied newspapers.